Adjournment of cases with special reference to practice in Industrial Court - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2009)
Where a case has been fixed for mention or hearing it is incumbent on the parties to ensure compliance by attending the proceeding on the date ascertained. The parties are expected to fully prepare their case and must be ready to proceed for the hearing. They must assist the court in the smooth conduct of the trial without the unnecessary interruptions of adjournment. If the court is satisfied that despite the exhaustive efforts made to ensure appearance, for example, the company or its authorised representatives fails to apper on the date ascertained...